2020
DOI: 10.3390/microorganisms8101534
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Bacteria from Alternative Fermented Foods as Starter Cultures for the Production of Wheat Sourdoughs

Abstract: Microbial strains for starter culture-initiated sourdough productions are commonly isolated from a fermenting flour–water mixture. Yet, starter culture strains isolated from matrices other than sourdoughs could provide the dough with interesting metabolic properties and hence change the organoleptic properties of the concomitant breads. Furthermore, the selection of sourdough starter cultures does not need to be limited to lactic acid bacteria (LAB), as other food-grade microorganisms are sometimes found in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 85 publications
(161 reference statements)
0
11
0
Order By: Relevance
“…However, in all these cases, a continuous agitation was applied to provide oxygen for the AAB growth. Also, AAB may contribute to the coloration of the bread crumb, likely by the production of dihydroxy acetone, hence enabling to produce brown wheat breads (Comasio et al 2020b).…”
Section: Acetic Acid Bacteriamentioning
confidence: 99%
“…However, in all these cases, a continuous agitation was applied to provide oxygen for the AAB growth. Also, AAB may contribute to the coloration of the bread crumb, likely by the production of dihydroxy acetone, hence enabling to produce brown wheat breads (Comasio et al 2020b).…”
Section: Acetic Acid Bacteriamentioning
confidence: 99%
“…Recently, AAB have also been considered useful starters for the production of desired metabolites [7]. Accordingly, Acetobacter pasteurianus IMDO 386B and Gluconobacter oxydans 3 of 13 IMDO A845 strains were tested for type II sourdough production processes and the latter, in particular, had an attractive impact on the production of volatile organic compounds [7].…”
Section: Sourdough Technologymentioning
confidence: 99%
“…In addition to these microorganisms, Proteobacteria may also be present, specially at the beginning of fermentation [5,6]. Among them, acetic acid bacteria (AAB), such as those belonging to Gluconobacter sp., Acetobacter sp., and Komagataeibacter sp., allow faster acidification of the dough and influence the volatile attributes of the final product [7][8][9][10]. The indigenous microflora of sourdough is the result of the microbial interaction among microorganisms coming from the flour, the bakery environment, and the vegetable matrices, such as fruits, must, or vinegar, which can be added to the original mixture to accelerate the start-up of fermentation [11].…”
Section: Introductionmentioning
confidence: 99%
“…For the determination of the total titratable acidity (TTA), 10 g of freeze-dried sourdough was mixed with 90 mL of distilled water. TTA was evaluated using an automatic titrator (TitroLine Easy, Schott Instruments, Mainz, Germany) and the results were expressed as the volume of NaOH 0.1N (mL) required to reach the pH value of 8.5 [53,54].…”
Section: Materials Microorganisms and Culture Conditionsmentioning
confidence: 99%
“…Our results suggested that an extension of the incubation time up to 96 h could result in higher levels of TTA, depending on the LAB strains used as inoculum. In a work from Comasio et al [54], the TTA values above 10.0 mL NaOH 0.1N were obtained with some selected Lactobacillus spp. strains, after 72 h of fermentation at 30 • C of a wheat-based sourdough.…”
Section: Selection Of the Most Important Fermentation Parameters By Plackett-burman Design (Pbd)mentioning
confidence: 99%